Case Report: 3 cases of abdominal lesions with lower limb lymphedema—rare mutations in complex lymphatic anomalies - Zhang, Yujia; Jiang, Yaxin; Qiu, Tong; Yang, Congxia; Yang, Min; Chen, Siyuan; Ji, Yi (Frontiers in Oncology, 2025)
Complex lymphatic anomalies (CLAs) are rare vascular anomalies characterized by abnormal proliferation of lymphatic and blood vessels, often resulting in multisystem involvement with heterogeneous clinical manifestations. We present 3 patients with CLAs exhibiting overlapping features of lower limb lymphedema and intra-abdominal vascular malformations, a phenotypic combination infrequently described in literature. Circulating tumor DNA (ctDNA) analysis in 2 cases detected somatic mutations at significantly higher variant allele frequencies compared to population databases, and mutant genes that were previously rare in vascular diseases were reported. These noninvasive molecular findings demonstrate diagnostic utility in identifying novel genotype-phenotype associations, providing insights into disease mechanisms and informing therapeutic strategies for atypical CLAs presentations. Our observations highlight ctDNA as a promising tool for refining diagnosis and guiding personalized management in rare vascular anomalies.